Ethics as an art of living: reflections at “Galileo Galilei” educational institution - Ojeda Ruiz, Francy Cathalina (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Ethics as an art of living arises from Foucault’s studies related to self-care, which openly confronts power centred on the organization of individualsunder certain norms, considering that subjects can shape themselves in opposition to the subjection or attempt to form a defined identity. Dialoguedreflections are presented with teachers of the “Galileo Galilei” Educational Institution (Tunja, Colombia) together with the analysis of practices anddiscourses, to recognize the elements of ethical constitution under this perspective. It is a qualitative research of interpretive approach, which highlightsmeeting points such as freedom, selfgovernment and democracy among others, and some divergences such as conformist thinking and monitoring ofmeaningless norms.